East Kalimantan Program - Herman Darman (Ikatan Ahli Geologi Indonesia, 2011)
The East Kalimantan Programme (EKP) aims to enhance and support long term scientific cooperation in coastal zone research between research groups from Indonesia and the Netherlands.The Research Cluster: